Recent Publications (Quarterly Journal of Economics, 1951)
Recent Publications The Quarterly Journal of Economics, Volume 65, Issue 4, November 1951, Pages 603–606, https://doi.org/10.1093/qje/65.4.603 Published: 01 November 1951